Аналіз видів проекцій та їх застосування у технічному кресленні - Колокольчева, С. А. (ХНУРЕ, 2023)
The principles of technical drawing are examined in this essay, in particular the several projection kinds. Axonometry and orthogonal projections are the two basic forms of projections that are covered. The distinctions between these two kinds of predictions, as well as how they are used in different industries, are thoroughly covered in the essay